(untitled) (Journal of Parents and Teachers, 2013)
Students from Telefónica Graduate and Repsol foundation for family and adisability wanted to transmit their experiences as students in the programs called: Assistant technician in Educative environments and Assitant in Technologic environments, taking place in Universidad de Comillas.